Ethical Challenges in The Development and Implementation of Artificial Intelligence and Emerging Technologies - Kim, Kang-Hyun; Neza, Violeta; Chung, Jun-Ki; Saifnazarov, Ismail; Kieliszek, Zdzislaw (International Journal of Basic and Applied Sciences, 2025)
The purpose of the study is to examine the moral contradictions arising in the context of the development of new technologies, with a focus on ethical aspects and possible consequences of their application. Methods of analysis, synthesis, generalization, and systematisation are used to achieve this goal. As a result of the study, it is established that the integration of artificial intelligence into various fields, such as the construction industry, healthcare, and finance, leads to substantial progress in efficiency and effectiveness. However, this progress is accompanied by complex ethical issues such as data privacy, bias, and job displacement. The need to consider ethical principles and social consequences is becoming increasingly important to ensure the responsible use of artificial intelligence and mitigate its potential risks. Solving ethical dilemmas requires the active interaction of various stakeholders and the development of reliable principles based on public values. In general, the adoption of new technologies should be based on a balanced approach that considers their advantages and potential negative consequences in the context of public welfare.